2002
DOI: 10.1016/s0967-0645(02)00328-4
|View full text |Cite
|
Sign up to set email alerts
|

A regional tidal/subtidal circulation model of the southeastern Bering Sea: development, sensitivity analyses and hindcasting

Abstract: A regional eddy-resolving primitive equation circulation model was used to simulate circulation on the southeastern Bering Sea (SEBS) shelf and basin. This model resolves the dominant observed mean currents, eddies and meanders in the region, and simultaneously includes both tidal and subtidal dynamics. Circulation, temperature and salinity fields for years 1995 and 1997 were hindcast, using daily wind and buoyancy flux estimates, and tidal forcing derived from a global model. This paper describes the devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 43 publications
3
28
0
Order By: Relevance
“…For example, tidal forcing induces a strong clockwise circulation around the Pribilof Islands (Fig. 7a), which is qualitatively in agreement with Kowalik and Stabeno (1999) and Hermann et al (2002). Without tidal forcing, such a clockwise circulation is not simulated (Fig.…”
Section: B Ocean Circulation and Transports Tidal Effects And Modesupporting
confidence: 71%
“…For example, tidal forcing induces a strong clockwise circulation around the Pribilof Islands (Fig. 7a), which is qualitatively in agreement with Kowalik and Stabeno (1999) and Hermann et al (2002). Without tidal forcing, such a clockwise circulation is not simulated (Fig.…”
Section: B Ocean Circulation and Transports Tidal Effects And Modesupporting
confidence: 71%
“…This may also help account for the simulated agreement with ice cover observations despite tidal forcing not being included in this simulation as a driving process for mixing and current rectification in the shallow waters of the Bering Sea (Hermann et al 2002;Zhang et al 2010).…”
Section: Methodsmentioning
confidence: 96%
“…It does not include tidal forcing. Earlier numerical studies have found that tidal forcing increases vertical mixing and the kinetic energy of ocean currents in the southeastern Bering Sea (Hermann et al 2002), as well as modifying sea ice thickness in the central-eastern Bering Sea (Zhang et al 2010). Tidal forcing might also reduce the mean flow due to the horizontal gradient of tidal mixing (Auad and Miller 2008).…”
Section: Methodsmentioning
confidence: 98%
“…Gorbatenko (2001) recorded T. inspinata in 1998 from the north-western Bering Sea. Apparently, the species has been transported by the Aleutian North Slope Current and the Bering Slope Current, which originates in the eastern Aleutians (Stabeno et al, 1995;Hermann et al, 2002). Nemoto & Kamada (1980) and Taki & Kotani (1994) recorded Thysanoessa inspinata in cold waters underlying the Kuroshio but not in the warmer northward £owing Kuroshio.…”
Section: Discussionmentioning
confidence: 96%